The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1017/s0021932007002532
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Antenatal Care and Its Dose–response Relationship With Birth Weight in a Maternal and Child Health Training Institute in Bangladesh

Abstract: Four hundred and sixty-five pregnant women and their newborn babies were studied at a maternal and child health training institute in Dhaka, Bangladesh, between July 2002 and June 2003 with the objective of (1) examining the relationship between birth weight and maternal factors, and, if there was a dose-response relationship between quality of antenatal care and birth weight, (2) predicting the number of antenatal visits required for women with different significant characteristics to reduce the incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…Unlike several studies that witnessed the beneficial effect of ANC in reducing the burden of LBW [9], [40], [41], the current study did not observe parallel findings. This might have to do with the inferior quality of ANC in the locality where only 42% and 76% of the ANC attendants received iron supplementation and nutrition education, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike several studies that witnessed the beneficial effect of ANC in reducing the burden of LBW [9], [40], [41], the current study did not observe parallel findings. This might have to do with the inferior quality of ANC in the locality where only 42% and 76% of the ANC attendants received iron supplementation and nutrition education, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…This study also found that there was an increase in birth weight as educational status of pregnant women increased from no education or primary education to secondary education and above. This is also supported by studies conducted in Bangladesh and Beirut [ 26 , 27 ]. In contrary to maternal education that had positive association to birth weight, multi parity or grand multi parity of mothers and older age of the mother (≥ 35 years) had negative association with birth weight.…”
Section: Discussionsupporting
confidence: 74%
“…The Maternal and Child Health Manual of Trinidad and Tobago deals specifically with these variables and it is ideally suggested that the first clinic visit be before 16 completed weeks and that there should be at least nine clinic visits (21). In this study, there was a significant correlation between birthweight and the number of visits as supported by recent research (42). There was no such correlation with week of first/booking visit as also shown in the Kramer meta analysis (25).…”
Section: Maternal Agesupporting
confidence: 86%